Formulasi Dan Evaluasi Sediaan Shampo Ekstrak Etanol Daun Cengkeh (Syzygium Aromaticum L) Sebagai Penumbuh Rambut Pada Tikus Putih Jantan - Manuppak Irianto Tampubolon; Dhea Nur Fadhilah; Dumartina Hutauruk (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Clove leaves have the property of overcoming hair growth problems, where the eugenol compound contained in clove leaves is efficacious as a hair growth agent. This research was conducted to formulate a clove leaf extract shampoo preparation. The research method used was the experimental method. Tests were carried out on experimental animals, namely male white mice in various groups. The first group (without treatment), the second group (negative control), the third group (5% clove leaf extract shampoo), the fourth group (10% clove leaf ethanol extract shampoo), the fifth group (15% clove leaf ethanol extract shampoo) and groups sixth (positive control). The shampoo preparations were tested and evaluated, the results of the preparation evaluation test showed that the four shampoo preparations were homogeneous and had a pH ranging from 5.1-5.7, with a viscosity of 1700-3000 cps and a foam height of 9-11 cm. This shampoo preparation also does not irritate the skin. The results of the data analysis obtained showed that all data were normally distributed (p> 0.005) and homogeneous (p> 0.005). The results of the one way ANOVA test show that F1 (5% formula), F2 (10% formula) and F3 (15% formula) have significant differences. This research shows that clove leaf ethanol extract shampoo with a concentration of 15% is the most effective formulation in hair growth in male white rats. However, the ethanol extract of clove leaves shampoo is less effective than minoxidil 5% for hair growth.